EKSPRESI TGF-B DAN MMP-1 PADA PERIODONTITIS APIKALIS KRONIS AKIBAT INDUKSI BAKTERI ENTEROCOCCUS FAECALIS TIKUS WISTAR - Tamara Yuanita; Hadriany Hotmaria; Ruslan Effendy; Ketut Suardita (Conservative Dentistry Journal, 2017)
Background. The main etiology of endodontic treatment failure  is caused by bacteries that stay in the root canal. E.faecalis is a bactery that is found as an etiology of endodontic treatment failure. Cell wall of this bacteria is containing Lipoteichoic acid (LTA). LTA can penetrate into the periradicular tissue, act as endotoxin in host and cause periradicular inflammation and destruction. It occurs due to the capability of TGF-ß to enhance the proliferation collagen and MMP-1 to stop the collagen formation. The ability of enterococcus faecalis in enhancing inflamation process cause host can not reach the homeostasis phase and performing an even bigger tissue damage. Purpose. The aim of this study is to know about the expression of of TGF-ß and MMP-1 during the periapical tissue damage due to induction of E.faecalis. Method. This study used laboratory experimental with the post test only control group design. A total of 27 male rats were randomly divided into 3 main groups. Group A (negative control) : every tooth was’nt induced by anything. Group B ( positive control): every tooth was induced only by sterile BHIb and closed by GIC Fuji II as the final restoration. Group C (: every tooth was induced by 10 μl BHI-b E.faecalis ATCC212(106 CFU), and closed by GIC Fuji II as the final restoration. The animals were sacrificed after 21 days and prepared for histological examination of tissue damage, then we did the immunohistochemistry  followed by calculation on the light microscope. Result. The analysis revealed that the expression of MMP-1 increased significantly in group C when E.faecalis was induced. When expression of TGF-ß decreaced significantly in group C rather than group B.  Conclusion. From this study we know that the expression of TGF-ß and MMP-1 are make opposite pathway due to chronic apical periodontitis that induced by E.faecalis.